Haplotype Structure and DNA Sequence Variation of the Liver Expressed Antimicrobial Peptide-2 (chLEAP-2) Gene in Chickens challenged with Eimeria maxima - Adikari , A.M.J.B.; Xu, J.; Casterlow, S.; Li, H.; Gilbert, E.R.; McElroy, A.P.; Emmerson, D.A.; Dalloul, R.A.; Wong, E.A.; Smith, E.J. (International Journal of Poultry Science, 2017)
Objective: The aim of this study was to screen the chLEAP-2 gene for DNA sequence variation and to evaluate the relationships among its haplotypes (based on haplogroups), expression levels, weight gain and lesion score in two chicken lines challenged with Eimeria maxima. Methodology: A total DNA sequence of 4.6 kb including the chLEAP-2 gene was screened by re-sequencing of individual amplicons. Sixteen SNPs, including seven each in the promoter and introns and two in exons, were identified. Results: One of the exonic single-nucleotide polymorphism (SNPs) was non-synonymous, involving a cysteine to tyrosine codon change. About 25% of the SNPs were in Hardy Weinberg equilibrium. Linkage disequilibrium (D’) among the SNPs ranged from 0.02-1.00. The haplotypes observed from the 16 SNPs were assembled into 5 haplogroups. The estimated frequencies of the haplogroups ranged from 0.17-0.23 in the combined chicken lines. Although not significant (p>0.05), the chLEAP-2 gene expression varied among haplogroups. Differences among haplogroups for lesion score and weight gain were consistent, but not statistically significant (p>0.05). However, Hap4 appeared to be the haplogroup least susceptible to coccidiosis. At a minimum, the data do not support an association between chLEAP-2 DNA sequence variation and symptoms of coccidiosis such as weight gain depression and lesion score. Conclusion: Therefore, earlier reports of differences between resistant and susceptible lines in chLEAP-2 expression may be due to trans-acting factors. The genomic results reported here provide resources for testing the trans-expression control theory and will be useful for future genotype:phenotype evaluation studies between chLEAP-2 and other traits in the chicken.